2010
DOI: 10.1002/anie.201002987
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Palladium/Triphosphane System for Direct Arylation of Heteroarenes with Chloroarenes at Low Catalyst Loading

Abstract: Palladium-catalyzed cross-coupling reactions between organometallic nucleophilic reagents and electrophilic organic halides or pseudohalides emerged as powerful synthetic tools for the construction of C À C bonds.[1-2] Such catalytic coupling processes are applied to a wide array of fields, which range from biological sciences to materials chemistry. [3][4] Their applications to heteroaromatic substrates set the stage for convergent synthetic routes to valuable substituted heterocyclic structures.[5] Because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(36 citation statements)
references
References 83 publications
1
31
0
3
Order By: Relevance
“…We had previously observed that with this pyrrole derivative a high yield of 89% could be obtained in the presence of only 0.5 mol % of a triphosphine associated to Pd(OAc) 2 as the catalyst [27]. With complexes 2 , 3 , 8 and 9 , a high conversion of 4-chlorobenzonitrile ( 11 ) and good yields of the coupling product 16 were obtained (Table 1, entries 1–9).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We had previously observed that with this pyrrole derivative a high yield of 89% could be obtained in the presence of only 0.5 mol % of a triphosphine associated to Pd(OAc) 2 as the catalyst [27]. With complexes 2 , 3 , 8 and 9 , a high conversion of 4-chlorobenzonitrile ( 11 ) and good yields of the coupling product 16 were obtained (Table 1, entries 1–9).…”
Section: Resultsmentioning
confidence: 95%
“…However, there are still limitations for these reactions in terms of aryl halide or heteroaromatic tolerance. Up to now, very few examples of palladium-catalyzed direct arylations of pyrroles by using aryl chlorides have been reported, [2627]. Daugulis and co-workers recently described the arylation of pyrrole derivatives with a variety of aryl chlorides using 5 mol % of Pd(OAc) 2 associated to 10 mol % of Cy 2 P- o -biphenyl as the catalyst [26].…”
Section: Introductionmentioning
confidence: 99%
“…The use of a particular ferrocenyl triphosphine in the direct arylation of heteroarenes with aryl chlorides that allowed low palladium loadings was described by Doucet and co-workers [21]. The couplings were carried out in DMA at 150 C for 16 h, employing 2.0 equiv.…”
Section: Direct Arylations Of Heteroarenes With Aryl Chloridesmentioning
confidence: 99%
“…Estes haletos orgânicos são os menos reativos de sua série, mas são também os mais baratos, justificando assim o esforço de levar a metodologia até sua aplicação final. Roy e colaboradores, 15 por exemplo, realizaram a arilação de diversos anéis heteroaromáticos na presença de 0,5 mol% de Pd(OAc) 2 e de um ligante do tipo fosfina. As reações foram feitas em N,N-dimetilacetamida (DMAc), com aquecimento a 150 °C por 16 h. Os rendimentos variaram entre 15 e 93%, para os diversos casos (Esquema 3).…”
Section: Inovação: Porque a Ativação C-h Vem Transformando A Química unclassified